Lower prosthesis-specific 10-year revision rate with crosslinked than with non-crosslinked polyethylene in primary total knee arthroplasty: 386, 104 procedures from the Australian Orthopaedic Association National Joint Replacement Registry. (2nd November 2015) - Steiger, Richard N de; Muratoglu, Orhun; Lorimer, Michelle; Cuthbert, Alana R; Graves, Stephen E
Abstract : Background and purpose — While highly crosslinked polyethylene has shown reduced in vivo wear and lower rates of revision for total hip arthroplasty, there have been few long-term studies on its use in total knee arthroplasty (TKA). We compared the rate of revision of non-crosslinked polyethylene to that of crosslinked polyethylene in patients who underwent TKA for osteoarthritis. Patients and methods — We examined data from the Australian Orthopaedic Association National Joint Replacement Registry on 302, 214 primary TKA procedures with non-crosslinked polyethylene and 83, 890 procedures with crosslinked polyethylene, all of which were performed for osteoarthritis. The survivorship of the different polyethylenes was estimated using the Kaplan-Meier method and was compared using proportional hazard models. Results — The 10-year cumulative revision rate for non-crosslinked polyethylene was 5.8% (95% CI: 5.7–6.0) and for crosslinked polyethylene it was 3.5% (95% CI: 3.2–3.8) (> 6.5-year HR = 2.2 (1.5–3.1); p < 0.001). There was no effect of surgical volume or method of prosthesis fixation on outcome. There were 4 different TKA designs that had a minimum of 2, 500 procedures in at least 1 of the polyethylene groups and a follow-up of ≥ 5 years. 2 of these, the NexGen and the Natural Knee II, had a lower rate of revision for crosslinked polyethylene. The Scorpio NRG/Series 7000 and the Triathlon Knee did not show a lower rate of revision for crosslinked polyethylene. Interpretation — There is a lower rate of revision for crosslinked polyethylene in TKA, and this appears to be prosthesis-specific and when it occurs is most evident in patients < 65 years of age. The difference in revision rates was mainly due to revisions because of lysis and loosening.